(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sobri MF, Jaaman SA, Mohamed Z, Muda AM, Rashid MASA, Zhang X. 2022. Identifying the hotspot area of Indo Pacific humpback (Sousa chinensis) and Irrawaddy (Orcaella brevirostris) dolphins in Matang waters, Perak, Malaysia. Biodiversitas 23: 6106-6113. The Indo-Pacific humpback (Sousa chinensis) and Irrawaddy (Orcaella brevirostris) dolphins are commonly found in Matang waters, Perak, Malaysia. The area, filled with healthy mangrove forest cover and many estuaries, is not only frequented by the dolphins for its daily activities but also extensively used by locals for artisanal fishing, charcoal production and organizing ecotourism activities. There could be a high risk of human-dolphin interactions, hence determining habitat use and identifying critical habitats or "hot spots" for the dolphins in the area is important. In this study, a series of dedicated boat sighting surveys were conducted from March 2019 to January 2021 between Kuala Gula and Kuala Jarum Mas. The total survey effort was 3325.76 km, 44 days and 239.38 hours. A total of 69 dolphin sightings were made, consisting of 40 Indo-Pacific humpback dolphins and 29 Irrawaddy dolphin observations, respectively. During each sighting, every dolphin’s behaviors were categorized as: foraging, socializing, evasive, and travelling, and the survey area was classified into four blocks. The results indicated that different dolphin species have different hotspot areas. For Indo-Pacific humpback dolphins, the hotspot area was Kuala Sangga, while the Irrawaddy dolphin’s hotspot area was outside Kuala Larut, and there was a small overlap between the two dolphins’ hotspots. Among the recorded behaviors (n: 281) for both dolphins, the most dominant was foraging (72.24%), followed by socializing (17%), evasive (7%), and travelling (4%). The sighted foraging behavior for both dolphin populations was dominant, indicating the hot spots were major foraging grounds for the two dolphin populations. This study shows the importance of Matang waters as a conservation area for the species and warrants further studies of dolphin population ecology to be conducted.